(3QSGdI aj CaYd EPG cGf ddJaVjds ((3GdcJHNGfI GdNOjhjI (B- (3eUQ s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf EYde Cf dGaYd EPG cGf ddJaVjd KdGKI CMhGd GdChd Cf jchf eYg ef fMh RjO CaVd ef YeQh hGdKGfi Cf JONd Ydjg GdCda hGddGe fMh RjO GdCaVd s
(3BNQgG (B:s
(3hCTO bhS HjfgG ai CaYd ef cPG ChdG Tc Cf GdLejY ai Mce CaYd GdJaVjd hGddg CYde JeJ HMeO Gddg hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs